Bibliometric Analysis of Land Use and Cover Changes Due to Oil Palm Expansion in Indonesia - Moh Fitrah Rawuh; Hadi Susilo Arifin; Andrea Emma Pravitasari (Universitas Muhammadiyah Palembang, 2026)
Land use and land cover changes in Indonesia, particularly those resulting from the expansion of oil palm plantations, are a critical issue in environmental dynamics and sustainable development. This study aims to analyze trends and characteristics of scientific publications related to LULCC in Indonesia using a bibliometric approach. Data were analyzed using VOSviewer and Biblioshiny to identify knowledge structures, thematic trends, and research topic developments. Results indicate that publications have experienced an annual growth rate of 9.68% with a relatively high level of collaboration. Dominant themes identified include land use, deforestation, and Indonesia, and suggest that in the literature, oil palm expansion is frequently associated with changes in land cover. Temporal analysis also indicates a shift in research focus toward issues of climate change, sustainability, and environmental monitoring. Overall, this study confirms that LULCC research in Indonesia is developing in a multidisciplinary manner and contributes to understanding research directions while supporting evidence-based policy-making.